Pengembangan Media Pembelajaran Berbasis Scratch Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak - Nabila Dewi Yulianti; Jasiah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Learning Aqidah Akhlak in Islamic Junior High Schools still faces challenges in facilitating the understanding of abstract concepts of faith and the internalization of moral values ​​​​in a meaningful way. Learning dominated by conventional methods tends to involve students less actively and has an impact on low learning outcomes. This study aims to develop and test the effectiveness of Scratch-based learning media in improving the learning outcomes of Aqidah Akhlak students in Islamic Junior High Schools. The study used a research and development method with the ADDIE model which includes the stages of needs analysis, design, development, implementation, and evaluation. The subjects of the study were 20 students of class IX-B MTs An-Nur Palangka Raya. Data were collected through learning outcome tests, student response questionnaires, and expert validation, then analyzed using normalized gain (N-gain) and descriptive statistics. The results showed that the use of Scratch media effectively improved student learning outcomes with an N-gain value of 0.68 (moderate category) and obtained positive responses of more than 80% in the aspects of interest, ease of understanding, and learning motivation. These findings demonstrate that Scratch contributes instructionally through visualization, interactivity, and feedback that support meaningful learning. This research provides a scientific contribution to the development of instructional design-based digital learning media for Aqidah Akhlak learning that is adaptive to the characteristics of learners in the digital era.